2018
DOI: 10.1007/s00251-018-1063-5
|View full text |Cite
|
Sign up to set email alerts
|

Cdx-2 polymorphism in the vitamin D receptor gene (VDR) marks VDR expression in monocyte/macrophages through VDR promoter methylation

Abstract: Caudal-type homeobox protein 2 (CDX-2) is an intestine-specific transcription factor (TF), with a polymorphic binding site (Cdx-2, rs11568820, A/G) in the vitamin D receptor gene (VDR). The molecular mechanism underlying Cdx-2 association with conditions like osteoporosis, which depends on intestinal VDR expression and calcium absorption, is believed to be due to higher affinity of CDX-2 for the ancestral A allele compared to the G allele. However, it is unclear why the polymorphism is associated with diseases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 39 publications
1
16
1
Order By: Relevance
“…Rs11568820 (Cdx2) VDR SNP was not assessed in AITD patients to date (according to the PubMed database, 31.04.2019). This SNP was previously shown to influence the immune system and modify the risk of some infectious diseases (e.g., tuberculosis and rubella) [17, 37, 38]. However, we did not observe a significant association between rs11568820 SNP and AIT risk.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…Rs11568820 (Cdx2) VDR SNP was not assessed in AITD patients to date (according to the PubMed database, 31.04.2019). This SNP was previously shown to influence the immune system and modify the risk of some infectious diseases (e.g., tuberculosis and rubella) [17, 37, 38]. However, we did not observe a significant association between rs11568820 SNP and AIT risk.…”
Section: Discussioncontrasting
confidence: 94%
“…Another candidate SNP of VDR that has not been yet studied in AIT is rs11568820 (Cdx2). This functional SNP, located in the promoter region of VDR , has been found to affect the immune system [17]. Therefore, the study aimed to assess the relationship between these five VDR SNPs (rs2228570, rs1544410, rs7975232, rs731236, and rs11568820) and AIT susceptibility in the Caucasian Polish population.…”
Section: Introductionmentioning
confidence: 99%
“…Cdx2 is considered as a functional polymorphism of the VDR gene that has been demonstrated to impact the immune system alter the risk of contracting certain infectious illnesses ( e.g. , tuberculosis and rubella) ( Meyer and Bornman, 2018 ; Ovsyannikova et al, 2010 ). Nevertheless, no substantial link has been established between this SNP and autoimmune disorders such as T1D, MS, vitiligo, or psoriasis ( Dickinson et al, 2009 ; Zhou et al, 2014 ; Frederiksen et al, 2013 ; Aydıngöz et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, no substantial link has been established between this SNP and autoimmune disorders such as T1D, MS, vitiligo, or psoriasis ( Dickinson et al, 2009 ; Zhou et al, 2014 ; Frederiksen et al, 2013 ; Aydıngöz et al, 2012 ). Although it is uncertain why the polymorphism is connected to illnesses like tuberculosis, numerous studies have connected this association to VDR methylation, vitamin D-mediated control of chemokine-positive T cells, and impact adaptive cytokine responses ( Meyer and Bornman, 2018 ; Ovsyannikova et al, 2010 ; Harishankar and Selvaraj, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation as an important epigenetic regulator plays a key role in gene expression 19 . Studies suggested that increased methylation of the VDR promoter was associated with decreased mRNA and VDR protein 20,21 . Methylation variation of the VDR promoter had been reported to be associated with cancer 20,22 .…”
Section: Introductionmentioning
confidence: 99%